Penggunaan Model Numbered Heads Together Dapat Meningkatkan Hasil Belajar Menjelaskan Bilangan Bulat Negatif Pada Siswa Kelas VI - Nugroho, Teguh (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this Classroom Action Research is that the use of the Numbered Heads Together model can improve class VI SDN 2 Sugihan students in the 2019/2020 school year. This research was conducted in two cycles and each cycle consisted of three meetings. The procedure in each cycle includes the following steps: 1) planning, 2) implementation, 3) observation, 4) reflection. The test result data explaining negative integers was analyzed by comparing the test scores between cycles until the results reached the completion limit according to the performance indicators. The action research carried out in two cycles showed that the average pre-cycle was 58.5 completeness 35%, the first cycle was 70 60% complete, the second cycle 80 was 95% complete. Based on the actions taken, it can be concluded: The use of the Numbered Heads Together model can improve learning outcomes to explain negative integers by 60% of VI grade students of SDN 2 Sugihan for the 2019/2020 school year by 35%.